The apex of the fetishism: administration, education and social control - Korstanje, Maximiliano E (Nómadas. Critical Journal of Social and Juridical Sciences, 2017)
ABSTRACT This paper discusses, as an essay configuration, the way by which the so-called "scientific management" fits in a socio-technical schemeof creation and ideological reinforcement in favor of the Capital and its reproduction. Through Marxist tradition, starting at ideology’s standpoint in Marx and through contemporary authors such as Adorno, Horkheimer, Marcuse, Fromm, Mészáros and Žižek, it is intended here to show how the allegedly administration scientific discourse provides mechanisms for full fetishization and reification of the subject, making it docile instrument of control of the Capital and maintenance and reproduction of the capitalist order. Keywords: Administration; Ideology; Fetishism; Domination.